Isolation Of Microcrystalline Cellulose From Oil Palm Empty Fruit Bunch Bleached Pulp: Statistical Optimization Of Acid Hydrolysis And Characterization - Hamzah, Tuan Muhamad Hassan Tuan (2018)
The optimization the acid hydrolysis process parameters condition for the production of microcrystalline cellulose (MCC) from oil palm empty fruit bunch (OPEFB) evaluated by using response surface methodology via central composite design. The OPEFB was first subjected to the environmental friendly pulping and bleaching sequence for the production of total chlorine free pulp prior to the acid hydrolysis process. Meanwhile for the optimization, a set of experiment was performed using three different factors which are time, temperature and acid concentration were carried out. The range of 10 to 30 min, 80 to 130 ºC and 1.5 to 3.5 N have been used for the variable. Meanwhile, yield %, thermal stability and crystallinity index of the resultant OPEFB-MCC were evaluated as the responses and were compared with the predicted values. Based on the optimization process conditions for MCC production were at hydrolysis time= 20 min, temperature= 106 ºC and acid concentration= 2.5 N, respectively. The OPEFB-MCC with high yield (92.2 %), good thermal stability (335.33 ºC) and crystallinity index (72.88 %) were obtained through this condition. The resultant OPEFB-MCC from optimized condition was then characterized by means of morphological, physiccochemical, crystallinity index and thermal study by using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), Brunauer–Emett–Teller (BET), X-ray diffraction (XRD) analysis, and thermogravimetric analysis (TGA).